1ISG-006 Hepatitis C treatment: cost and effectiveness. (March 2019) - Brito, A; Fernandes, A; Lourenço, L; Domingos, S; Soares, A; Alcobia, A
Abstract : Background: The hepatitis C virus (HCV) infection is one of the major causes of chronic liver disease. Due to the HCV infection prevalence in European regions (1.5%), increasing health expenditure has been made in order to eradicate HCV. Purpose: Assess the cost, effectiveness and safety of treated HCV patients with pegylated interferon-ribavirin (IFN-RIB) compared to new direct acting antivirals (DAA). Material and methods: Retrospective observational comparative study of two cohorts of patients including HCV patients who started and finished treatments with IFN-RIB in 2011 (except the above 12 months) and with DAAs in 2017. Exclusion criteria: deaths, no therapeutic adherence and transfer to another hospital. Data were extracted from electronic records. Results: In 2011, 49 patients (87.8% male) with a mean age 44.4±7.1 years were included: 12.2% were previously treated, 40.8% co-infected and genotypes 1 was predominant (51.0%), and 73.5% were treated with IFNα2a-RIB and the remaining with IFNα2b-RIB. In 2017, 185 patients (75.0% male) were included, with a mean age 52.2±9.9 years, 28.1% co-infected. Genotype 1 (64.9%) was the most common: 79.3% patients had severe or moderate fibrosis (FD ≥2). Only 11.4% were previously treated (four with DAA). Treatments were: 71.9% Ledipasvir/Sofosbuvir; 7.6% Sofosbuvir/Velpatasvir; 7.0% Sofosbuvir; 7.0% Elbasvir/Grazoprevir; 3.2% Ombistasvir/Paritaprevir/Ritonavir+Dasabuvir; 2.2% Daclatasvir +Sofosbuvir; 0.5% Sofosbuvir +Ombistasvir/Paritaprevir/Ritonavir+Dasabuvir; and 0.5% Ombistavir/Paritaprevir/Ritonavir. Comparing treatments of two cohort patients (IFN-RIB/DAA): in 2011 average treatment length was 8.1 months/patient much longer than 2017 (3.5 months/patient) and 12 weeks' length in 70.4%. In 2011, drug discontinuation occurred in 36.7% treatments because the patients had serious adverse reactions (AR) or were non-responders. In 2017, DAA had fewer and lower severity AR (100% compliance). According to guidelines' alterations, eight patients had shortened their initial duration of treatment. Treatments with IFN-RIB (€4287.7/patient) were less expensive than DAA (€14867.1/patient), representing an increase of €1309.2% annually. Although the success rate was significantly higher with DAA (96.8%) than with IFN-RIB (53.1%), 23/49patients, in 2011, were posteriorly treated with DAA. The incremental cost-effectiveness ratio (DAA/IFN-RBV) was €238.1/patient successfully treated. Costs are higher, but, in 2018, the costs of treatment/patient are half that of 2017. Conclusion: DAA treatments have higher effectiveness against HCV infection(>95%) and treatments are shorter, more effective and safer than older therapies, despite higher costs. Reference and/or acknowledgements: WHO Guidelines for the screening, care and treatment of persons with chronic HCV infection 2016. No conflict of interest.